STUDY OF IMMUNOHISTOCHEMICAL TECHNIQUES FOR PLACENTA IN PLACENTA - Ruah F. Al-mayahi; Fawzi S. AL-Asadi (Basrah Journal of Veterinary Research)
The present study which include the demonstration of estrogen and progesteronereceptors and demonstration of CD34 protein in placenta of pregnant sheep. Twentyone placenta from pregnant sheep were used in the present study. Theimmunohistochemical study of CD34 protein as marker for vascularization appear atday (27) few distribution in stroma of villi While at day (50) of gestation high densityof CD34 protein in And also showed at day (120) high density. The estrogen receptorshowed colour by kit at day (27) normal distribution in trophoblast cell of villusepithelium and not present in binucleate cell While at day (50) high density ofestrogen receptor was showed ,And also at day (120) show high density of estrogen.The immunohistochemical study of progesterone receptor as appear at day (27)normal distribution in trophoblast cell of placentome and not present in binucleate cellWhile at day (50) high density, and also at day (120) .